Recursive methods in economic dynamics - Stokey, Nancy L.; Lucas, Robert E., Jr; Prescott, Edward C. (Harvard University Press, 1989)
Develops the basic methods of recursive analysis, covers stochastic dynamic programming, and presents two fundamental theorems of welfare economics.